2018
DOI: 10.1159/000492724
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Asymptomatic Brain Natriuretic Peptide Elevation at Nephrology Referral in Patients with Chronic Kidney Disease

Abstract: Background: It is unclear whether asymptomatic elevation of brain natriuretic peptide (BNP) is associated with cardiovascular events (CVEs) or heart failure (HF) in predialysis chronic kidney disease (CKD) patients. Methods: We measured BNP in 482 asymptomatic predialysis patients with CKD stages 2–5 at nephrology referral between August 2004 and October 2010, and followed them prospectively to investigate the prognostic significance of BNP using Cox models and receiver operating characteristic (ROC) analyses.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Moreover, in patients with stage 4-5 CKD, a BNP concentration >157 pg/mL was identified as an independent risk factor for a cardiovascular event; however, the sensitivity and specificity were only 65% and 56%, respectively [28]. It has also been shown that, in patients with end-stage renal failure, but without clinical symptoms of HF, the detection of BNP levels >150 pg/mL before starting renal replacement therapy was an independent risk factor for overt HF [29].…”
Section: What Is the Practical Significance Of Bnp And Nt-probnp In Patients With Advanced Ckd?mentioning
confidence: 99%
“…Moreover, in patients with stage 4-5 CKD, a BNP concentration >157 pg/mL was identified as an independent risk factor for a cardiovascular event; however, the sensitivity and specificity were only 65% and 56%, respectively [28]. It has also been shown that, in patients with end-stage renal failure, but without clinical symptoms of HF, the detection of BNP levels >150 pg/mL before starting renal replacement therapy was an independent risk factor for overt HF [29].…”
Section: What Is the Practical Significance Of Bnp And Nt-probnp In Patients With Advanced Ckd?mentioning
confidence: 99%
“…Brain natriuretic peptide has been shown to be associated with a composite end point of time to death or the 1st cardiovascular event but not with all-cause mortality in CKD [13]. In The African American Study of Kidney Disease and Hypertension, proBNP was associated with cardiovascular events and cardiovascular mortality in 994 patients with eGFR 20–65 mL/min/1.73 m 2 , but not with all-cause mortality [30].…”
Section: Discussionmentioning
confidence: 99%
“…Biomarkers such as troponin T (TnT), N-terminal pro-B-type natriuretic peptide (proBNP), high-sensitivity C-reactive protein (CRP), interleukin-6, and serum albumin have been studied as prognostic factors in CKD with mixed results. Previous studies have shown an association between TnT, proBNP, and cardiovascular events and death and between serum albumin and all-cause mortality in CKD patients [11-13]. However, cardiac biomarkers have not been associated with all-cause mortality in previous studies [13, 14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation